2017
DOI: 10.5588/ijtld.16.0270
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric and adolescent tuberculosis in Latvia, 2011–2014: case detection, diagnosis and treatment

Abstract: TB case detection through contact investigation provided early diagnosis and excellent treatment outcomes in children and adolescents in Latvia. CT was able to identify pathology consistent with subclinical TB in children with a history of exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…In the 1990's, CT scans revealed greater detail and coined the term “tree-in-bud” sign as the characteristic feature of advancing pulmonary TB ( 65 67 ). In the past few years, this has been confirmed by studies in South Africa and Latvia using CT and PET-CT ( 22 , 40 , 45 ).…”
Section: Functions Of Primary and Post-primary Tbmentioning
confidence: 64%
“…In the 1990's, CT scans revealed greater detail and coined the term “tree-in-bud” sign as the characteristic feature of advancing pulmonary TB ( 65 67 ). In the past few years, this has been confirmed by studies in South Africa and Latvia using CT and PET-CT ( 22 , 40 , 45 ).…”
Section: Functions Of Primary and Post-primary Tbmentioning
confidence: 64%
“…The early pulmonary infiltrate, Assmann’s focus, is the lesion that represents the onset of PPTB, Figure 4 [ 54 ]. Worldwide interest in its significance stimulated numerous studies and publications through the 1940s and beyond [ 43 , 44 , 46 , 48 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. Multiple investigations confirmed that the early pulmonary infiltrate was a common onset of TB.…”
Section: X-rays Of Developing Tbmentioning
confidence: 99%
“…The median number of contacts undergoing advanced imaging was relatively small, at 32. Twelve studies examined children to adolescents [ 13 – 16 , 18 , 21 , 23 – 25 , 27 , 28 , 30 ], while the other studies included adults. One study was conducted on contacts infected with HIV [ 35 ], while the other 24 studies were conducted in immunocompetent contacts.…”
Section: Main Textmentioning
confidence: 99%
“…One study was conducted on contacts infected with HIV [ 35 ], while the other 24 studies were conducted in immunocompetent contacts. Four studies partly [ 25 , 29 ] or entirely [ 23 , 26 ] included close contacts with drug-resistant TB. Bacterial and molecular testing with sputum or other specimens (e.g., gastric aspirates) generally yielded a low positivity rate in contacts with minimal CT or PET abnormalities, reflecting a low bacillary burden (Table 1 ).…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation